ECONOMIC ASPECTS OF GREEN ECONOMY DEVELOPMENT IN UZBEKISTAN - Gulyamov S.S; Baxodirov A.A; Mamatakhunov N.A; Rasulova M.T; Salmetova U.H (Scholar Express Journals, 2025)
Due to the economic growth in Central Asian countries, the issue of alternative energy sources instead of complex hydroelectric power plants has often been raised recently. For example, recently in many countries around the world, solar panels, wind turbines, and incinerators have been used more often to generate energy. Our country has signed agreements with the world's leading companies on the construction of factories for the production of solar panels and wind turbines. They will be installed mainly in the southern regions of the Republic where high temperatures are observed.
Keywords: green energy; heating batteries